Informing pregnancy dose via target‐mediated drug disposition modeling and simulations for a recombinant human monoclonal antibody - Courtney Moc Willeford; Krithika Shetty; Douglas Sheridan; Frank Engler (Wiley, 2024)
Abstract RLYB212 is a human monoclonal anti‐human platelet antigen (HPA)‐1a immunoglobulin gamma 1 in clinical development as a subcutaneous injection for the prevention of maternal alloimmunization to fetal HPA‐1a leading to fetal and neonatal alloimmune thrombocytopenia (FNAIT). This analysis developed a target‐mediated drug disposition (TMDD) model to simultaneously characterize RLYB212 pharmacokinetics (PK) and HPA‐1a‐positive platelet dynamics in HPA‐1b/b (HPA‐1a‐negative) volunteers. The model was then used to perform simulations to inform a dosing regimen in a phase II clinical study in pregnant women, where simulations accounted for physiological changes throughout pregnancy. Allometric scaling (0.75) for clearance and intercompartment transfer rate and volume (1) was included in the base model to account for variations in body weight. A 0.06 mg RLYB212 dose with a loading dose of 0.12 mg was identified as the optimal dosing regimen of RLYB212, which maintained exposures below the target upper boundary of ~10 ng/mL throughout pregnancy. This work presents an application of the TMDD model that advances the quantitative clinical pharmacology toolkit to understand monoclonal antibody PK in pregnancy.